The lexical barrowing in between languagesSome samples of Arabic words travelling to the Spanish language (مجلة إحالات, 2026)
This research aims at shedding light on the lexical borrowing that is a natural linguistic phenomenoncaused by the linguistic contact that all human language witness all different levels : geographic plolitic and even social it’s totally obvious all civilizations though out time that’s why each of them deponds on the otherin terms of creation and transfer . In fact, as far as languages are known by their flexibility and opening there is always a linguistic lexisrich of new words and terms in different fields and specialities mainly nowadays as we are living a high level of technological growth that lead languages to contact each other by means of the linguistic borrowing mean wile it is necessary that each language should follow this phenomenon with a great deal by reference to itsofficial linguistic institutions. This study would present some sample of Arabic words sorrowed by Spanish language so as to demonstrate the so far stated phenomenon.